Treatment of severe tricuspid regurgitation induced by permanent pacemaker lead: Transcatheter tricuspid valve replacement with the guidance of 3-dimensional printing - Mao, Yu; Liu, Yang; Meng, Xin; Ma, Yanyan; Li, Lanlan; Zhai, Mengen; Jin, Ping; Lu, Fanglin; Yang, Jian (Frontiers in Cardiovascular Medicine, 2023)
Background: Lead-induced tricuspid regurgitation is one of the complications after permanent pacemaker implantation (PPI) and refers to tricuspid regurgitation (TR) caused by the lead in the right ventricle (RV). Objectives: To study the clinical characteristics of severe TR after PPI and the effect of transcatheter tricuspid valve replacement (TTVR) with the guidance of 3-dimensional (3D) printing. Methods: This study was a single-center, descriptive study. Six patients with severe TR after PPI were enrolled in Xijing Hospital from January 2020 to May 2020. Before TTVR, the 3D printed tricuspid valve (TV) model was used for evaluation in the bench test. LuX-Valve was implanted under the guidance of TEE and X-ray fluoroscopy, and all patients underwent transatrial access. Six patients’ data were collected at baseline, before discharge, and 6 months, 1 year and 2 years after TTVR. Results: The LuX-Valve was successfully implanted in 6 patients, TR was significantly reduced to ≤2+, and no deaths or external circulation surgeries occurred during procedures. Three cases were caused by TV expansion: Patient #4 had TR caused by lead adhesion to TV, Patient #2 had TR caused by lead winding, and Patient #6 had TR caused by lead impingement on TV. During the 2-year follow-up, TTE revealed that 5 patients had no/trace regurgitation, and one patient (Patient #5) had mild regurgitation. All 6 patients (100.0%) reached primary endpoints. Conclusion: TTVR guided by 3D printing is safe and effective in the treatment of severe TR associated with permanent pacemaker lead, providing prospects and possibilities for the precise treatment of TV-related diseases.